Results of judo rehabilitation for people with intellectual disabilities - Case reports of judo training in Japan - Tokuyasu, H.; Okada, R.; Okazaki, Y.; Koyama, K.; Moriwaki, Y.; Hashimoto, N. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
This study reports on the contents of judo training and rehabilitation provided to people with intellectual disabilities at two special needs education schools in Japan. First, Warashibe-Kai, which started in 2010 in Osaka, has fostered activities for improving physical strength and spending one`s leisure time by training courteously while supporting those with mild intellectual disabilities aiming to start work. Second, Judo has been taught since 1969, when it was incorporated into the physical education curriculum at The Tokyo Metropolitan Seicho Special Needs Education School in Tokyo. These case reports reveal that Judo training has positive physical and mental effects on people with intellectual disabilities.